2018
DOI: 10.1590/1678-4324-2018180195
|View full text |Cite
|
Sign up to set email alerts
|

Azo Dye Mineralization by Phanerochaete Chysosporium in a Sequencing Bath Reactor

Abstract: The mineralization of the azo dye congo red by the fungi Phanerochaete chrysosporium was studied in two sequential batch bioreactors (R1 and R2), operated in cycles of 48 h (step I) and 24 h (step II). In step I, glucose concentration was 1 g.L -1 in both reactors and in step II, 1 g.L -1 of glucose was maintained in R1, but R2 received no addition of glucose. In step I, the average dye removal efficiencies were 76 ± 29 % (R1) and 53 ± 15% (R2), while in step II the averages recorded for dye removal for R1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The combi-CLEA particles improved the degradation of the textile effluents (Acid Violet 7 (from 45.2% to 93.4%) and Basic Fuchsin (from 12.1% to 67.9%). Using the fungi P. chrysosporium , Wanderley et al [ 195 ] reported the transformation of the azo dye Congo Red in two sequential batch bioreactors operated in cycles of 24 h and 48 h. In this case, laccase enzymes were produced in higher amounts. Sierra-Solache et al [ 196 ] reported on the utilization of the P. chrysosporium strain EMIM 5 in global wastewater treatment of textile effluents based on bioremediation and ultrafiltration processes.…”
Section: Bioremediation By White Rot Fungimentioning
confidence: 99%
“…The combi-CLEA particles improved the degradation of the textile effluents (Acid Violet 7 (from 45.2% to 93.4%) and Basic Fuchsin (from 12.1% to 67.9%). Using the fungi P. chrysosporium , Wanderley et al [ 195 ] reported the transformation of the azo dye Congo Red in two sequential batch bioreactors operated in cycles of 24 h and 48 h. In this case, laccase enzymes were produced in higher amounts. Sierra-Solache et al [ 196 ] reported on the utilization of the P. chrysosporium strain EMIM 5 in global wastewater treatment of textile effluents based on bioremediation and ultrafiltration processes.…”
Section: Bioremediation By White Rot Fungimentioning
confidence: 99%
“…Enhanced techniques are evidently the pre-condition for accelerated elimination of azo dyes, because any residual contaminants should be removed completely. Fungi have been investigated, especially those secreting non-specific oxidases which eventually lead to the azo dyes mineralization into CO2 (Wanderley et al 2018). Fungal degradation (Mycoremediation) also leads to complete decoloration and detoxification, which prevents sludge removal and secondary contamination issues.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi, particularly secreting non‐specific oxidases and leading to mineralization of azo dyes into carbon dioxide, have been explored (Wanderley et al . 2018). Degradation by these fungi often leads to complete decolourization as well as detoxification evading the trouble of sludge removal and secondary pollution.…”
Section: Introductionmentioning
confidence: 99%